The XMM deep survey in the Chandra Deep Field South. Issue 2 (20th March 2017) - Comastri, A.; Iwasawa, K.; Vignali, C.; Ranalli, P.; Lanzuisi, G.; Gilli, R.
Abstract : The Chandra Deep Field South (CDF‐S) was observed by XMM‐Newton for about 3 Ms in many periods over the past decade (2001–2002 and 2008–2009). The main goal of the survey was to obtain good quality X‐ray spectroscopy of the active galactic nuclei responsible for the bulk of the X‐ray background. We present the scientific highlights of the XMM‐Newton survey and briefly discuss the perspectives of future observations to pursue XMM deep survey science with current and forthcoming X‐ray facilities.